Porous brazing filler metal film for brazing hard alloy and stainless steel and preparation method of porous brazing filler metal film
By preparing porous brazing film, the welding problem caused by the difference in thermal expansion coefficient when welding cemented carbide and stainless steel is solved, and the strength and wear resistance of the joint are improved, which is suitable for brazing joints of different shapes.
Patent Information
- Application Number
- CN202411665280.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The welding of cemented carbide and stainless steel has large differences in thermal expansion coefficients, which leads to welding problems, limiting the wider use of cemented carbide.
A porous brazing film is prepared by mechanical mixing and metallurgical alloying method, adding pore-forming agent and compounding manganese and cobalt elements to prepare a nickel-copper active brazing film with low melting point, good wetting and high toughness.
Reduces residual stress of welded joints, improves the strength and wear resistance of joints, optimizes the reliability of brazed joints, and is suitable for brazed joints of different shapes.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, in particular to a porous brazing material film for brazing hard alloy and stainless steel and a preparation method thereof. Background Art
[0002] Cemented carbide has excellent properties such as high hardness, wear resistance, heat resistance, corrosion resistance and good red hardness. It is widely used in industrial fields such as mechanical processing, geological exploration, and mining. However, the disadvantage is that cemented carbide has poor toughness and processability, and its application range is limited. The welding of cemented carbide and steel can well solve the shortcomings of cemented carbide such as limited size, simple shape, high cost, and poor toughness, expand the application range of cemented carbide, and has important practical value. The complex components formed by it are widely used in projects such as oil drilling, mining and space exploration. The brazing method is used to connect cemented carbide and stainless steel, which has the advantages of stable metallurgical bonding and high mechanical properties, and has practical application research prospects.
[0003] At present, most cemented carbides are brazed and embedded in medium carbon steel or stainless steel substrates. The brazing performance directly affects the use of cemented carbide. Since the thermal expansion coefficients of cemented carbide and steel are very different, the welding problem has always hindered the wider use of cemented carbide. The present invention aims to study a porous brazing film with low melting temperature and excellent wettability. The present invention provides a porous brazing film for brazing cemented carbide and stainless steel and a preparation method thereof. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a porous brazing material film for brazing cemented carbide and stainless steel and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing a porous brazing material film for brazing cemented carbide and stainless steel, comprising the following steps;
[0006] (1) Weigh the raw materials
[0007] A binder, a surfactant, a plasticizer and a solvent are weighed in a mass ratio of 1:0.8:0.8:6-15 to obtain a mixed slurry, and 5-10 wt.% of a pore-forming agent is added to the metal powder to obtain a mixed powder;
[0008] (2) Tape casting
[0009] The mixed slurry and mixed powder are placed in a sealed container at a mass ratio of 1:2-5, mixed in a powder mixer for 10-24 hours to obtain a uniform slurry, and the slurry is evenly scraped on a stainless steel plate with a scraping film, with a scraping thickness of 100-1000um. The stainless steel plate is placed in a nitrogen atmosphere and dried for 2-3 hours before taking the film;
[0010] (3) Sintering
[0011] The film is placed in a vacuum sintering furnace for sintering treatment, and then ultrasonically cleaned to obtain a solder film with a certain toughness, which is then cut and rolled as needed.
[0012] Preferably, the metal powder in step (1) is composed of the following components in weight percentage: 50% to 60% Cu, 10% to 20% Ni, 0% to 4% Mn, 0% to 10% Co, and the balance Zn. All powders are spherical powders with a particle size of 1 to 100 microns and a purity higher than 99.8%.
[0013] Preferably, the pore-forming agent in step (1) is one or more of carbon particles, polystyrene microspheres, polymethyl methacrylate microspheres, inorganic ammonium salts, and potassium sulfate.
[0014] Preferably, the binder is PVB, the surfactant is Tween-20, the plasticizer is PEG or glycerol; and the solvent is alcohol.
[0015] Preferably, the brazing heating method used includes but is not limited to induction brazing, vacuum brazing, resistance brazing, and furnace brazing.
[0016] Preferably, the specific steps of the sintering process are:
[0017] The vacuum molybdenum sheet sintering furnace is heated to 200°C to 300°C at a heating rate of 1°C / min to 10°C / min and kept at this temperature for 60 to 360 minutes;
[0018] Then, the temperature is raised to 350°C to 400°C at a heating rate of 1°C / min to 10°C / min and kept at this temperature for 60 to 360 minutes;
[0019] Then, the temperature is increased to 450°C to 500°C at a heating rate of 1°C / min to 10°C / min and kept at that temperature for 60 to 360 minutes; then, the temperature is increased to 600°C to 800°C at a heating rate of 1°C / min to 10°C / min and kept at that temperature for 60 to 120 minutes;
[0020] Then heat up to 800℃~950℃ at a heating rate of 1℃ / min~10℃ / min and keep it at that temperature for 60~240min. After the heat preservation, cool down to 500℃~600℃ at a cooling rate of 1℃ / min~5℃ / min and keep it at that temperature for 60~360min. After the heat preservation, cool down to room temperature with the furnace.
[0021] The invention discloses a method for preparing a porous solder film for brazing hard alloy and stainless steel. The porous solder film is prepared.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The porous solder film prepared by the present invention is a solder for brazing hard alloy and stainless steel. Based on nickel-copper active solder, manganese and cobalt elements are added in combination to modify the alloy solder, wherein nickel is a strengthening element, and can achieve solid solution strengthening with copper element, improve the wear resistance of the alloy solder, nickel element and manganese element can improve the strength of the joint, and zinc element can reduce the welding temperature and improve the wettability of the solder. The prepared solder film is soft and tough, with a smooth surface, and the thickness can be controlled within 100 to 600 microns, and can be curled for storage and punched into any shape. It can adapt well to different brazing joint shapes, and the thickness during use can be controlled by scraping the film thickness or rolling, so as to facilitate the control of the usage amount. The solder has the characteristics of good wettability, low melting point, brazing temperature range of 850 to 950°C, narrow solid-liquid temperature range, no residue after melting, good joint shear resistance and good wear resistance, etc. The present invention adopts a method of mechanical mixing and metallurgical alloying to prepare a porous alloy solder film, the preparation method has a simple process flow, is conducive to mass production, has the advantages of low energy consumption, simple operation, high production efficiency, and easy control of alloy composition and dosage, etc. The porous solder film of the present invention is applied to brazing a composite material prepared by YG8 cemented carbide and 316 stainless steel, and has a good effect, and the shear strength of the joint reaches 423.26-546.58MPa. DETAILED DESCRIPTION
[0024] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The method for preparing the porous brazing material film for brazing cemented carbide and stainless steel of this embodiment comprises the following steps:
[0026] (1) Weigh the raw materials
[0027] A binder, a surfactant, a plasticizer and a solvent are weighed in a mass ratio of 1:0.8:0.8:6-15 to obtain a mixed slurry, and 5-10 wt.% of a pore-forming agent is added to the metal powder to obtain a mixed powder;
[0028] (2) Tape casting
[0029] The mixed slurry and mixed powder are placed in a sealed container at a mass ratio of 1:2-5, mixed in a powder mixer for 10-24 hours to obtain a uniform slurry, and the slurry is evenly scraped on a stainless steel plate with a scraping film, with a scraping thickness of 100-1000um. The stainless steel plate is placed in a nitrogen atmosphere and dried for 2-3 hours before taking the film;
[0030] (3) Sintering
[0031] The film is placed in a vacuum sintering furnace for sintering treatment, and then ultrasonically cleaned to obtain a solder film with a certain toughness, which is then cut and rolled as needed.
[0032] In step (1) of this embodiment, the metal powder is composed of the following components in weight percentage: 50% to 60% Cu, 10% to 20% Ni, 0% to 4% Mn, 0% to 10% Co, and the balance Zn. All powders are spherical powders with a particle size of 1 to 100 microns and a purity higher than 99.8%.
[0033] In step (1) of this embodiment, the pore-forming agent is one or more of carbon particles, polystyrene microspheres, polymethyl methacrylate microspheres, inorganic ammonium salts, and potassium sulfate.
[0034] In this embodiment, the binder is PVB, the surfactant is Tween-20, the plasticizer is PEG or glycerol; and the solvent is alcohol.
[0035] The brazing heating methods used in this embodiment include but are not limited to induction brazing, vacuum brazing, resistance brazing, and furnace brazing.
[0036] The specific steps of the sintering process in this embodiment are:
[0037] The vacuum molybdenum sheet sintering furnace is heated to 200°C to 300°C at a heating rate of 1°C / min to 10°C / min and kept at this temperature for 60 to 360 minutes;
[0038] Then, the temperature is raised to 350°C to 400°C at a heating rate of 1°C / min to 10°C / min and kept at this temperature for 60 to 360 minutes;
[0039] Then, the temperature is increased to 450°C to 500°C at a heating rate of 1°C / min to 10°C / min and kept at that temperature for 60 to 360 minutes; then, the temperature is increased to 600°C to 800°C at a heating rate of 1°C / min to 10°C / min and kept at that temperature for 60 to 120 minutes;
[0040] Then heat up to 800℃~950℃ at a heating rate of 1℃ / min~10℃ / min and keep it at that temperature for 60~240min. After the heat preservation, cool down to 500℃~600℃ at a cooling rate of 1℃ / min~5℃ / min and keep it at that temperature for 60~360min. After the heat preservation, cool down to room temperature with the furnace.
[0041] The porous brazing material film prepared by the method for preparing a porous brazing material film for brazing cemented carbide and stainless steel in this embodiment.
[0042] Example 1
[0043] The porous solder film described in this embodiment is prepared according to the following steps:
[0044] 1. Prepare slurry
[0045] PVB, Tween-20, PEG, and alcohol are weighed in a mass ratio of 1:0.8:0.8:8 to obtain a mixed slurry; 5wt.% potassium sulfate is added to the metal powder to obtain a mixed powder; the mixed slurry and the mixed powder are placed in a closed container in a mass ratio of 1:4 and mixed in a powder mixer for 10 to 24 hours to obtain a uniform slurry. The metal powder is composed of the following components in weight percentage: 60% Cu, 10% Ni, 3% Mn, 5% Co, and the balance Zn. All powders are spherical powders with a particle size of 48 microns and a purity higher than 99.8%.
[0046] 2. Tape casting
[0047] Mix in a powder mixer for 24 hours to obtain a uniform slurry. Use a film scraper to evenly scrape the slurry onto a stainless steel plate with a scraping thickness of 500 um. Place the stainless steel plate in a nitrogen atmosphere and dry it for 3 hours before taking a film.
[0048] 3. Sintering
[0049] The film was placed in a vacuum sintering furnace, and the temperature was increased to 250°C at a heating rate of 10°C / min, and kept warm for 120 minutes. The temperature was then increased to 400°C at a heating rate of 2°C / min, and kept warm for 240 minutes. The temperature was then increased to 500°C at a heating rate of 2°C / min, and kept warm for 240 minutes. The temperature was then increased to 800°C at a heating rate of 5°C / min, and kept warm for 60 minutes. The temperature was then increased to 850°C at a heating rate of 5°C / min, and kept warm for 180 minutes. After the insulation, the temperature was reduced to 600°C at a cooling rate of 2°C / min, and kept warm for 60 minutes. After the insulation, the film was cooled to room temperature with the furnace, and ultrasonic cleaning was performed to obtain a solder film with a certain toughness, which was cut and rolled as needed.
[0050] The average shear strength of the joint obtained by brazing YG8 cemented carbide and 316 stainless steel with the porous brazing material film of this embodiment at 920° C. for 10 minutes is 482.63 MPa.
[0051] Example 2
[0052] The porous solder film described in this embodiment is prepared according to the following steps:
[0053] 1. Prepare slurry
[0054] PVB, Tween-20, PEG, and alcohol are weighed in a mass ratio of 1:0.8:0.8:10 to obtain a mixed slurry; 5wt.% potassium sulfate is added to the metal powder to obtain a mixed powder; the mixed slurry and the mixed powder are placed in a closed container in a mass ratio of 1:3 and mixed in a powder mixer for 20 hours to obtain a uniform slurry. The metal powder is composed of the following components in weight percentage: 55% Cu, 8% Ni, 4% Mn, 5% Co and the balance Zn. All powders are spherical powders with a particle size of 10 microns and a purity higher than 99.8%.
[0055] 2. Tape casting
[0056] Mix in a powder mixer for 24 hours to obtain a uniform slurry. Use a film scraper to evenly scrape the slurry onto a stainless steel plate with a scraping thickness of 500 um. Place the stainless steel plate in a nitrogen atmosphere and dry it for 3 hours before taking a film.
[0057] 3. Sintering
[0058] The film was placed in a vacuum sintering furnace, and the temperature was increased to 250°C at a heating rate of 10°C / min and kept for 120 minutes, and then increased to 400°C at a heating rate of 2°C / min and kept for 240 minutes, and then increased to 500°C at a heating rate of 2°C / min and kept for 240 minutes, and then increased to 800°C at a heating rate of 5°C / min and kept for 60 minutes, and then increased to 900°C at a heating rate of 5°C / min and kept for 180 minutes. After the insulation, the film was cooled to 600°C at a cooling rate of 2°C / min and kept for 60 minutes. After the insulation, it was cooled to room temperature with the furnace, and ultrasonic cleaning was performed to obtain a solder film with a certain toughness, which was cut and rolled as needed.
[0059] The average shear strength of the joint obtained by brazing YG8 cemented carbide and 316 stainless steel with the porous brazing material film of this embodiment at 910°C for 10 minutes is 503.48 MPa.
[0060] The present invention discloses a porous solder film for brazing hard alloy and stainless steel and a preparation method thereof. The preparation method comprises the following steps: uniformly mixing solder metal powder, pore former and binder, performing tape casting with a scraper to obtain a solder film with a thickness of 100 to 600 microns, and performing vacuum sintering and ultrasonic cleaning to obtain the porous solder film. The brazing temperature range of the porous solder film is 850 to 950°C, the texture is flexible, it can be curled for storage and punched into any shape, it has a narrow solid-liquid temperature range, and there is no residue after melting. For hard alloy and stainless steel with large differences in thermal expansion coefficients, the porous solder film prepared by the present invention can reduce the residual stress of the brazed joint, improve the joint strength, and optimize the problem of poor reliability of the brazed joint.
[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a porous brazing material film for brazing cemented carbide and stainless steel, characterized in that: The steps include: (1) Weigh the raw materials A binder, a surfactant, a plasticizer and a solvent are weighed in a mass ratio of 1:0.8:0.8:6-15 to obtain a mixed slurry, and 5-10 wt.% of a pore-forming agent is added to the metal powder to obtain a mixed powder; (2) Tape casting The mixed slurry and mixed powder are placed in a sealed container at a mass ratio of 1:2-5, mixed in a powder mixer for 10-24 hours to obtain a uniform slurry, and the slurry is evenly scraped on a stainless steel plate with a scraping film, with a scraping thickness of 100-1000um. The stainless steel plate is placed in a nitrogen atmosphere and dried for 2-3 hours before taking the film; (3) Sintering The film is placed in a vacuum sintering furnace for sintering treatment, and then ultrasonically cleaned to obtain a solder film with a certain toughness, which is then cut and rolled as needed.
2. The method for preparing a porous brazing material film for brazing cemented carbide and stainless steel according to claim 1, characterized in that: The metal powder in step (1) is composed of the following components in weight percentage: 50% to 60% Cu, 10% to 20% Ni, 0% to 4% Mn, 0% to 10% Co, and the balance Zn. All powders are spherical powders with a particle size of 1 to 100 microns and a purity higher than 99.8%.
3. The method for preparing a porous brazing material film for brazing cemented carbide and stainless steel according to claim 1, characterized in that: In step (1), the pore-forming agent is one or more of carbon particles, polystyrene microspheres, polymethyl methacrylate microspheres, inorganic ammonium salts, and potassium sulfate.
4. The method for preparing a porous brazing material film for brazing cemented carbide and stainless steel according to claim 1, characterized in that: The binder is PVB, the surfactant is Tween-20, the plasticizer is PEG or glycerol; and the solvent is alcohol.
5. The method for preparing a porous brazing material film for brazing cemented carbide and stainless steel according to claim 1, characterized in that: The brazing heating methods used include, but are not limited to, induction brazing, vacuum brazing, resistance brazing, and furnace brazing.
6. The method for preparing a porous brazing material film for brazing cemented carbide and stainless steel according to claim 1, characterized in that: The specific steps of sintering treatment are: The vacuum molybdenum sheet sintering furnace is heated to 200°C to 300°C at a heating rate of 1°C / min to 10°C / min and kept at this temperature for 60 to 360 minutes; Then, the temperature is raised to 350°C to 400°C at a heating rate of 1°C / min to 10°C / min and kept at this temperature for 60 to 360 minutes; Then, the temperature is increased to 450°C to 500°C at a heating rate of 1°C / min to 10°C / min and kept at that temperature for 60 to 360 minutes; then, the temperature is increased to 600°C to 800°C at a heating rate of 1°C / min to 10°C / min and kept at that temperature for 60 to 120 minutes; Then heat up to 800℃~950℃ at a heating rate of 1℃ / min~10℃ / min and keep it at that temperature for 60~240min. After the heat preservation, cool down to 500℃~600℃ at a cooling rate of 1℃ / min~5℃ / min and keep it at that temperature for 60~360min. After the heat preservation, cool down to room temperature with the furnace.
7. A porous brazing material film prepared by the method for preparing a porous brazing material film for brazing cemented carbide and stainless steel as claimed in any one of claims 1 to 6.
Citation Information
Patent Citations
Radial bearing of screw rod drill
CN104088897A
Method for brazing stainless steel and cemented carbide through gradient material method
CN106862694A
Vacuum brazing YG8 hard alloy and 0Cr13 stainless steel solder
CN109664044A
Method for brazing graphite and titanium alloy through NiCu porous alloy interlayer
CN114029571A
Method for preparing stainless steel porous membrane and connecting stainless steel porous membrane with stainless steel pipe
CN114941137A